Formulation and Physical Evaluation of Peel Off Gel Mask Containing Nutmeg Seed (Myristica fragrans Houtt.) Extract with Different Polyvinyl Alcohol (PVA) Concentrations - Marsaoly, Adelia; Ambarwati, Neneng Siti Silfi; Atmanto, Dwi (Jurnal Biologi Tropis, 2026)
Polyvinyl alcohol (PVA) serves as a film-forming substance that significantly influences the physical properties of peel-off gel masks. Changes in the concentration of PVA can impact the formulation's quality, affecting factors like viscosity, ease of spreading, stickiness, and drying duration. The ethanolic extract of nutmeg seeds (Myristica fragrans Houtt.) is rich in flavonoids that possess antioxidant properties, making it an advantageous active component for the formulations of peel-off gel masks. This study aimed to formulate a peel-off gel mask containing nutmeg seed extract with different PVA concentrations (10%, 12%, and 14%) and to evaluate its physical characteristics. The extract was acquired through maceration with 96% ethanol, and its antioxidant ability was assessed by the DPPH method. The physical assessment involved examining organoleptic features, homogeneity, pH, viscosity, spreadability, adhesiveness, and drying duration. The results were evaluated using One-Way ANOVA or Welch ANOVA, along with Tukey's HSD or Games-Howell post hoc tests based on the data characteristics. The findings indicated that the nutmeg seed extract displayed exceptionally strong antioxidant abilities, with an IC₅₀ value of 9.648 ppm. An increase in PVA concentration led to higher viscosity, adhesiveness, and drying duration, while it decreased spreadability. All formulations fulfilled the standards for organoleptic features, homogeneity, pH, spreadability, adhesiveness, and drying time. Nonetheless, the formulation with 14% PVA had a viscosity slightly over the suggested standard range. From the overall initial physical assessment, the formulation with 12% PVA was regarded as the most well-balanced formulation. Nevertheless, this formulation exhibited a more turbid appearance than the formulation containing 10% PVA. Further studies, including physical stability and safety evaluations, are required to confirm its suitability as the optimal formulation.